Building Attendance Application with Location Based Service Technology and Waterfall Method to Overcome Long Attendance Queues and Reduce the Risk of Exposure to Covid-19 - Fajrianto, Rendi; Tarigan, Masmur (Journal of Intelligent Computing & Health Informatics, 2021)
Employee attendance using finger print attendance device, is not efficient enough for PT. Modern Gravure Indonesia, because it will result in long queues. In addition, attendance using a finger print attendance device can increase the risk of contracting COVID-19 disease, because there is physical contact. So a mobile-based application is needed in order to anticipate long attendance queues and avoid the risk of being exposed to COVID-19. This application provides an attendance feature with location validation using LBS technology. If the employee is already in the office area or less than 500 meters from the office coordinates, then he or she can take attendance, so the employee cannot commit fraud. This application can also display monthly reports that are used for integration with the PT. Modern Gravure Indonesia. The method used to build this application is Waterfall and UML diagram modeling. This application will be built using the Flutter framework. And for the server side it will be built using the Laravel framework. With this application, it is expected to be able to overcome long attendance queues and reduce the risk of being exposed to Covid-19 at PT. Modern Gravure Indonesia.